Eficiência das paradas de ônibus em Santa Maria, RS, avaliado a partir de geoprocessamento - Trindade, Patricia Michele Pereira (2014)
In this work we highlight the importance of urban planning, which finds in geoprocessing an ally to a spatial data analysis in the city. In this context, the objective of the present research is to analyze the suitability of the main bus stops in the urban transport in the city of Santa Maria. In order to achieve this goal, we have developed the following methodological steps: 1) bibliography review; 2) definition of the principal bus stops studied; 3) registration of the main bus stops; 4) after collected all bus stops, they were sent to the software ArcGIS Server Workgroup Standart 9.3; 5) it was drawn up a map for each bus routes containing the itinerary and its respective bus stops as well as the development of thematic maps with information about population density and income; 6) it was examined the infrastructure of each bus stop with the aim at classifying each bus stop according to the bibliography selected. In this sense, it was registered the following bus stops of the collective urban transport: Tancredo Neves, UFSM-Faixa Velha, Bombeiros-Faixa Velha, Santa Marta, Prado, Cohab Fernando Ferrari Faixa Nova e Faixa Velha, Alto da Boa Vista, 7 de Dezembro, UFSM-Faixa Nova, Tancredo Neves-Campus, Bombeiros-Faixa Nova, Camobi. As results, it was registered 347 bus stops and analyzed that most itineraries of bus stop routes are downtown and in East regions, demonstrating that the majority of people s displacement in those regions happens due to their jobs and studies. It was possible to find five sorts of bus stops: 29 bus stops with signposting and shelter, 139 with only shelter, 24 with shelter in bad conditions, 40 only with signposting and 115 with any identification. Considering the bibliography used in this research, 232 bus stops could be classified as formal bus stops and the rest of them as informal ones due to the fact that they did not present any kind of signposting. Taking into account physic aspects, 177 bus stops were classified as simple ones. Only 29 bus stops could be considered complete ones and in order to classify them as complex ones, they should have presented more equipment. Consequently, less than 1% of all bus stops analyzed presented all equipment. It is also important to highlight that the bus stops studied in this research with less infrastructure were located in areas of the city in which the responsible for the residence earns until 2 minimum wages. Bus stops with better structure presented only 8, 35% from the total amount of bus stops analyzed in the research.